PENGARUH PERSEPSI SISWA TENTANG KETERAMPILAN MENGAJAR GURU, FASLISITAS BELAJAR, PERGATIAN ORANG TUA, LINGKUNGAN SEKOLAH DAN MOTIVASI BELAJAR TERHADAP EFEKTIVITAS BELAJAR SISWA MATA PELAJARAN EKONOMI KELAS XI DI SMAN 3 SOLOK SELATAN - Wedi Wedi (Horizon, 2021)
This study aims to analyze, 1) the partial efekct of teacher teaching skills on student learning motivation, 2) the effect of learning facilities on student learning motivation, 3) the effect of parental attention on student learning motivation, 4) the influence of the school environment on student learning motivatin, 5) the effect of partially teaching teacher skills on the effectiveness of student learning, 6) the effect of learning facilities partially on the effectiveness of student learning, 7) the effect of parental attention partially on the effectiveness of student learning. 8) partially influencing the school environment on the effectiveness of student learning, 9) partially influencing learning motivation on the effectiveness of student learning. The results showed that (1) the variable teacher skills obtained a coefficient of tcount of 4.932> t Table (1.993) (2) the learning facilities variable obtained a coefficient of tcount of 4.519> t Table (1.99) (3) the variable parental attention obtained a coefficient value t count of 2.132> t Table (1.993) (4) The school environment variable obtained the t count coefficient of -5.490> tTable (1.993) (5) the teaching teacher skill variable obtained the t count coefficient of 1.931> t Table (1.993) (6) the learning facilities variable obtained t count coefficient value of -2,804> t Table (1,993), (7) variable parental attention obtained t count coefficient value of 2,675> t Table (1,993), (8) school environment variable obtained t count coefficient value of 2,056> t Table (1,993), (9) the learning motivation variable obtained t count coefficient of 3,350> t Table (1,993).